A Qualitative Analysis of Emotional Facilitators in Exercise - Wienke, Benjamin; Jekauc, Darko (Frontiers in Psychology, 2016)
Although previous research has shown that emotions are consistently associated with sport and exercise behavior, the working mechanisms are not understood to the extent of creating an intervention. The aim of this study is to identify situations and aspects of recreational sport and exercise, which lead to positive emotional reactions in people taking part in regular and long-term exercise. In this study, 24 adults (12 female, 12 male) distributed over three age groups (young, middle, and late adulthood), took part in recreational sports (individual or team sport) for at least 5 years. Semi-structured in depth interviews with questions about sport and exercise habits, long term participation and emotional response in a sporting environment were conducted in order to ascertain those situations and aspects of the exercise program triggering positive emotions. Interviews were transcribed verbatim and followed Grounded Theory principles. Emerging concepts were grouped and merged into different categories representing the key aspects of sport and exercise. Four factors were identified which are associated with the emergence of positive emotions in recreational sport and exercise. Firstly, perceived competence is one of the major factors influencing emotions during exercise and can represent individual and collective success and progress, competition and challenge. Secondly, perceived social interaction is another factor comprising of all sorts of peer-related aspects such as communication with others, being part of a group and creating close relationships or friendships. Thirdly, novelty experience in contrast to other none-sporting activities such as work, family or other leisure activities was another factor. The last factor found was the perceived physical exertion comprising of the degree of exhaustion, a possibly delayed turnaround in the emotional response and the aspect of sport being a physical compensation for everyday sedentary life. The results of this study provide the starting point for the development of interventions to enhance positive emotions in sports in order to increase maintenance and adherence to recreational sport and exercise.